“The modern way to loveliness”: middle-class cosmetics and chain-store beauty culture in mid-twentieth-century Britain - Hornsey, Richard (Taylor & Francis, 2018)
In May 1935, the British manufacturer Boots launched ‘Number Seven’, a premium range of skin-care products sold via its nationwide network of chain-store chemists. Using material from the Boots Archive, this paper traces the early history of Number Seven to explore the changing meanings of middle-class cosmetics across the mid-twentieth century. Number Seven offered provincial and suburban women an explicitly modern form of facial beauty that married the logics of mass production to traditional moral aesthetics. Through the discourse of ‘loveliness’ and the careful management of in-store experience, it negotiated the prerogative connotations of colour cosmetics and the problematic influence of cinematic glamour. Yet by the mid-1950s, this construction had been superseded by a more situational understanding of beauty that was dependent on context and the appreciation of others. This fundamental shift in the normative aesthetics of public femininity had important implications for women on both sides of Boots’ toilet counters.